PENGARUH PENDIDIKAN KESEHATAN TENTANG SENAM DIABETIK TERHADAP PENGETAHUAN PASIEN DIABETES MELITUS TIPE 2 DALAM MENCEGAH LUKA DIABETIK - Jamiatun; Dwi Puspitasari (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
As a result of the increased incidence of DM, complications from diabetes mellitus can occur, one of which can cause disability in the feet. It is important to provide health education to DM patients regarding leg movements to help prevent DM complications. The purpose of this study was to determine the effect of health education about diabetes exercise on the knowledge of type 2 diabetes patients about preventing diabetic foot injuries. This study used a pre-experimental design with a one-group pre-test-post-test approach. The study population consisted of patients diagnosed with type 2 DM and a sample of 17 people. Data was collected using a DM patient knowledge questionnaire about preventing diabetic foot wounds. The data analysis used was t-test analysis (paired sample t-test). Univariate analysis showed low knowledge before the intervention (47.1%) and high knowledge after the intervention (47.1%). Bivariate pair sample T-test analysis showed that health education had an effect on knowledge of DM patients (p=0.000). Therefore, it is hoped that health workers can continue to make modifications in providing health education to prevent diabetes mellitus that can be understood and practiced by patients and their families.